TINJAUAN ATAS PROSEDUR PEMBAYARAN UTANG USAHA PADA PT SOFTEX INDONESIA - Haikal Fairuzzaidan, (2022)
Payment of accounts payable is an accounting activity that is discussed in this final project. The purpose of writing this final project is to find out the parts, documents, and related functions in the trade payable payment procedure. And the method used is to observe directly how the trade payable payment procedure is carried out. The initial procedure for paying trade payables starts with the emergence of debt as a result of a purchase request from the warehouse to the purchasing department. The purchasing department issues a purchase order which will be submitted to the vendor for procurement of goods. The ordered goods will be sent by the vendor to the company's warehouse to be received and verified by the warehouse department. Documents related to delivery of goods to the warehouse, namely purchase orders and documents . After the goods are received, the warehouse department issues the receipt date sheet (TPB) as a reference for recording the debt. The process of recording debt is carried out by the accounting department based on documents received from vendors in the form of bills, travel documents, receipts of goods, purchase orders, and tax invoices. Then the treasury performs the payment process for the recorded debt. The results obtained from this writing is to gain knowledge of the procedures for paying accounts payable at PT Softex Indonesia.